2000
DOI: 10.1021/es9913986
|View full text |Cite
|
Sign up to set email alerts
|

Osmium Isotopes Demonstrate Distal Transport of Contaminated Sediments in Chesapeake Bay

Abstract: Because the isotopic composition of anthropogenic Os is normally distinctive in comparison to continental crust and is precisely measurable, this platinum-group element is attractive as a tracer of transport pathways for contaminated sediments in estuaries. Evidence herein and elsewhere suggest that biomedical research institutions are the chief source of anthropogenic Os. In the Chesapeake Bay region, uncontaminated sediments bear a crustal 187Os/188Os signature of 0.73 ± 0.10. Slightly higher 187Os/188Os rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…This material was collected from Tokyo Bay where both river water and seawater mix with tidal circulation. Some proportion of Os in this reference material may be derived from an anthropogenic source, as described in the United States by Esser and Turekian (1993) in New Haven harbor and by Helz et al (2000) in Chesapeake Bay. Anthropogenic Os has a low isotopic ratio of about 0.14 (Esser and Turekian, 1993;Ravizza and Bothner, 1996), because Osbearing materials used for industry and vehicles originate from ore deposits with low 187 Os/ 188 Os.…”
Section: Resultsmentioning
confidence: 99%
“…This material was collected from Tokyo Bay where both river water and seawater mix with tidal circulation. Some proportion of Os in this reference material may be derived from an anthropogenic source, as described in the United States by Esser and Turekian (1993) in New Haven harbor and by Helz et al (2000) in Chesapeake Bay. Anthropogenic Os has a low isotopic ratio of about 0.14 (Esser and Turekian, 1993;Ravizza and Bothner, 1996), because Osbearing materials used for industry and vehicles originate from ore deposits with low 187 Os/ 188 Os.…”
Section: Resultsmentioning
confidence: 99%
“…1). Point sources of anthropogenic Os include sewage outflow [17][18][19][20]22 incinerators 17,18,23 and smelters [24][25][26] , whereas automobile catalytic converter exhaust in densely populated regions can impart a significant regional influence 21,27,28 . On a global scale, the refining of PGE ores, coupled to the widespread use of catalytic converters, has driven the 187 Os/ 188 Os of precipitation and oceanic surface waters to more unradiogenic values 7 .…”
mentioning
confidence: 99%
“…Using laboratory analyses of sixteen different pesticides, they found that chlorothalonil had the highest concentration in the air, while wet deposition fluxes were highest for methyl parathion, malathion, metolachlor, and atrazine. Helz et al (2000) also investigated the Chesapeake Bay, concentrating on the use of osmium isotopes to investigate distal transport of contaminated sediment in the bay. A Mid-Bay sampling site showed the highest osmium levels, despite the long distance between this sampling location and the anthropogenic contamination sources as well as the northerly bottom currents with flows opposing the direction of transport.…”
Section: Measurementsmentioning
confidence: 99%